The Effect of Brand Equity, Brand Loyalty, Work Productivity, and Organizational Commitment on Consumer Satisfaction at the Coconut Research Center Medan Palm Oil - Wan Dian Safina; Emelia Rahmadhany; Danang Yanuar Wibowo; Frian Danil; Innayah Innayah; Ismiy Nurhabibah Harahap; Siti Virza Amalia (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the influence of brand equity, brand loyalty, work productivity, and organizational commitment on consumer satisfaction at the Medan Palm Oil Research Center. The research method used is a survey with data collection through questionnaires distributed to consumers who interact with the Medan Palm Oil Research Center. The results of this study are compiled based on data analysis conducted to test the influence of brand equity, brand loyalty, work productivity, and organizational commitment on consumer satisfaction at the Medan Palm Oil Research Center. This study involved 177 respondents who were consumers of products from the Medan Palm Oil Research Center. The results of the validity test shown in the table above obtained the results of the correlation coefficient with the highest validity of 0.9123 and the lowest correlation coefficient of 0.0520. The results of the validity test show that the correlation coefficient between the score of each instrument item and the total score of all statement items is greater than 0.3. This means that it can be concluded that all indicators in this study are declared valid. The results of the reliability test shown in Table 3 can be concluded that all of the instruments are reliable because the Cronbach's Alpha of each instrument is greater than 0.60 so that it can be used to conduct research.